2006
DOI: 10.1016/j.ejcts.2006.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Sampling or node dissection for intraoperative staging of lung cancer: a multicentric cross-sectional study

Abstract: Radical mediastinal dissection is a mandatory adjunct to resection for lung cancer with curative attempt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…TNM staging was also effective in predicting the outcome of pulmonary NET, similar to what Vallieres E reported (Vallieres et al, 2009) However, it was strange that nodal status did not predict the prognosis. A previous report showed that lymph node sampling might be inaccurate in evaluating the nodal status (Massard et al, 2006). Only 63.1% of patients in this study underwent the systemic nodal dissection, so it might underestimate the N stage.…”
Section: Discussionmentioning
confidence: 84%
“…TNM staging was also effective in predicting the outcome of pulmonary NET, similar to what Vallieres E reported (Vallieres et al, 2009) However, it was strange that nodal status did not predict the prognosis. A previous report showed that lymph node sampling might be inaccurate in evaluating the nodal status (Massard et al, 2006). Only 63.1% of patients in this study underwent the systemic nodal dissection, so it might underestimate the N stage.…”
Section: Discussionmentioning
confidence: 84%
“…MLND is reported to be more accurate in determining multilevel N2 disease and skip metastases. [10][11][12][13][14] Because two to fi ve lymph nodes were resected from each N2 station in the majority of patients in our study, it is likely that occult N2 disease would be discovered if present and, despite rigorous systematic sampling prior to randomization, 21 patients were found to have occult N2 disease with MLND.…”
Section: Discussionmentioning
confidence: 96%
“…The identification of malignant lesions amongst the many benign radiographic abnormalities remains a clinical challenge, and the optimal treatment of these cancers remains to be defined. While many surgeons have stressed the importance of systematic lymph node dissection and lobectomy [1][2][3][4], other investigators have suggested that limited resection with minimally invasive techniques may be done with equal efficacy in these selected patients [5,6].…”
Section: Introductionmentioning
confidence: 99%